ANALISIS PEMANFAATAN DANA PENSIUN TERHADAP PEMENUHAN KEBUTUHAN HIDUP PNS PENSIUNAN GURU KOTA MEDAN - Muhammad Fahmi Tanjung; Wahyu Ario Pratomo (Ekonomi dan Keuangan, 2013)
This study aims to analyze the use of pension funds for the substistence like needs for food, clothing, housing, health needs and their families and family needs. In this study, the data used are primary data by giving questionnaires to 50 respondents retired teacher in Medan. Respondents' answers will be used to answer whether pension funds can fulfill the needs life of PNS retired teacher in Medan. The analysis used is descriptive qualitative analysis. Data analysis techniques using data tabulation of frequency distribution and percentage. The results showed that pensioners living needs during retirement fulfilled. From the results of this research is the income received from pension funds are not sufficient to subsistence. Pensioners get extra income from children and other businesses. From the results of this research is that more pensioners choose to receive a pension funds once the whole than the receiving each month. Keywords: Retirement, basic needs, health needs, the family unit